Study on F-waves of median nerve in patients with compressed cervical radiculopathy - Nguyen, Thi Hieu Dung; Huynh, Vo Hanh Thao; Bui, Manh Hung; Phan, Thi Tuyet Nhung; Tran, Thi Kim Anh; Nguyen, Duy Duan; Le, Trong Binh; Nguyen, Thanh Minh; Nguyen, Dinh Toan (Tạp chí Y Dược Huế, 2025)
Background: Recent research has demonstrated that specific parameters derived from F-wave analysis can aid in the diagnosis of radiculopathy. The objective of this study is to assess the characteristics of F waves in upper extremity nerves of patients diagnosed with compressed cervical radiculopathy and explore the relationship between these F-wave characteristics and the degree of nerve root compression in magnetic resonance imaging. Methods: A cross-sectional study was conducted, comprising 16 control individuals and 47 patients with confirmed cervical root compression as determined by MRI. Nerve conduction velocity measurements of upper extremity peripheral nerves were performed in the electrodiagnostic room of the Functional Exploration Department at Hue University of Medicine and Pharmacy Hospital between June 2022 and May 2023. Results: Significant differences were observed in five indices - F-wave minimal latency, F-wave maximal latency, F-wave mean latency, F dispersion, and F persistence - between patients with low cervical radiculopathy (24 men and 23 women, mean age: 53.34 ± 10.52) and the control group (7 men and 9 women, mean age: 50.50 ± 16.50). When comparing these F-wave parameters with MRI images, only F-wave mean latency and F maximal latency demonstrated a correlation with the severity of nerve root compression (p < 0.05, r > 0.5). Conclusion: The findings suggest that F-wave parameters can serve as valuable tools in supporting the diagnosis of low cervical radiculopathy, even in the absence of changes in motor and sensory nerve conduction. Specifically, F-wave mean latency and F-wave maximal latency appears to be associated with the severity of cervical root compression.